Oral delivery of Kaempferia parviflora's methoxyflavones via nanostructured lipid carriers: Its effect on obesity and dyslipidemia treatment” - Natchanon Rimsueb; Peera Tabboon; Phichaporn Bunwatcharaphansakun; Uracha Ruktanonchai; Katawut Namdee; Udom Asawapirom; Bungorn Sripanidkulchai; Sarunya Tuntiyasawasdikul; Somsuda Somintara; Tawut Rudtanatip; Mattaka Khongkow (International Journal of Pharmaceutics: X)
Kaempferia parviflora extract (BG), commonly known as Black Ginger, is a plant native to Thailand and other Southeast Asian countries. Its methoxyflavones are active compounds widely used in dietary supplements. However, their oral administration faces challenges due to poor stability, low gastrointestinal bioavailability, and limited absorption. This study developed a nanostructured lipid carrier (NLC) encapsulating BG to enhance GI stability, bioavailability, and efficacy via oral administration. The BG-NLC exhibited a homogeneously spherical morphology with an average size of 99.15 ± 0.09 nm, a zeta potential of −25.37 ± 0.99 mV, and a PDI of 0.19 ± 0.01. The particles demonstrated high stability during storage at 4 °C, 25 °C, and 40 °C for three months, following Asian health supplement stability guidelines. Furthermore, BG-NLC showed excellent physicochemical stability in simulated gastric (SGF) and intestinal fluids (SIF), significantly enhancing intestinal absorption and permeability by approximately 10–30 % compared to BG. In vitro studies revealed that BG-NLC significantly reduced lipid accumulation and triglyceride production in differentiated adipocytes, surpassing the performance of BG. In vivo studies in a high fat-diet induced obesity mouse model further demonstrated improved BG bioavailability, resulting in reductions in body weight, body mass index (BMI), and liver and adipose tissue weights. In summary, BG-NLC exhibits high stability in simulated GI conditions, improved intestinal absorption, and notable anti-adipogenic effects, alongside potential benefits for blood sugar regulation. These findings highlight the potential of BG-NLC as a novel and effective formulation for health supplements and pharmaceutical products targeting metabolic-related diseases.